The Relationship between the Implementation of ERP Systems and the Financial and Non-Financial Reporting of Organizations - Laura-Eugenia-Lavinia Barna (MDPI AG, 2021)
Numerous studies have shown that ERP systems can improve organizational performance and efficiency. Thus, the main concepts addressed in the paper are ERP systems, their performance and the manner in which they improve financial and non-financial reporting. The purpose of this paper is to observe the relationship between ERP systems and financial reporting. The role of these systems is to ensure transparency over the financial and non-financial reporting process of an organization. The research method is represented by an archival analysis (organization’s annual reports) to highlight the relationship between ERP systems and financial and non-financial reporting, given the impact of ERP systems on the information used to prepare financial and non-financial reports and how the organization changes after implementing these systems. The results highlight the significant role of ERP systems within an organization, in terms of performance and improvements in financial and non-financial reporting.